Kirigami analogies for parallelogram-based remote-center-of-motion mechanisms - Bok Seng Yeow; Alex Wang; Chin-Hsing Kuo; Hongliang Ren (Biomimetic Intelligence and Robotics)
This paper presents a framework for applying origami-kirigami techniques to design kirigami analogies for remote center-of-motion (RCM) mechanisms, specifically targeting minimally invasive keyhole procedures. The proposed kirigami RCM analogs emulate the motions of existing bar-linkage RCMs, offering advantages in deployability, transportability, and simplified fabrication. A workflow is introduced to transition from initial crease patterns to functional kirigami equivalents, demonstrating the potential for customizability and scalability. Furthermore, a proof-of-concept kirigami RCM under magnetic actuation is presented, showcasing its ability to reduce structural profile during transportation and improve device deployment. Three representative parallelogram-based RCM mechanisms: coupled dual parallelogram, back-drivable, and triple parallelogram, are transformed into kirigami analogs, highlighting the versatility of the design approach. The discussion includes computational modeling, fabrication considerations, and potential applications in MIS robots. This work contributes to the development of compact, deployable, and cost-effective RCM mechanisms for robotic keyhole procedures. This approach can also further facilitate the education of RCM mechanisms and the hands-on demonstration of small-scale RCM concepts.